Advance Physics Virtual Laboratory (ADPHYLAB): Its Implication in Improving Students' Science Process Skills in Atomic Spectroscopy Practicum - Guntara, Yudi; Fitriani, Nur Shabrina; Tabrani, Rizqi A’mal Hibatullah; Tanjung, Winnei Ray Beatrix; Marwanti, Kissi; Wibowo, Firmanul Catur; Bunyamin, Muhammad Abd Hadi (FKIP Universitas Lampung, 2024)
Understanding the concept of physics students can not be achieved through lectures alone, but required practicum. However, limited equipment makes practicum difficult to do as an example of atomic spectroscopy. However, the use of information technology-based media in the form of virtual laboratories can be used as an alternative choice without losing its essence to facilitate Science Process Skills (SPS). This study aims to compare the improvement of students' SPS in atomic spectroscopy practicum using Advance Physics Virtual Laboratory (ADPHYLAB) and LABSTER. This research is a modified type of comparative research. The research time was conducted for 3 meetings, located in the Physics Laboratory of FKIP UNTIRTA. The research subjects were 8 physics laboratory assistants. The results showed that the SPS N-Gain score in the group using ADPHYLAB obtained consecutive values for classification, measurement, data interpretation and inferring indicators of 0.73; 0.89; 0.71 and 0.94, falling into the high category. While the group using LABSTER obtained scores on classification and measurement indicators of 0.40 and 0.53, falling into the medium category. While in the data interpretation and inferring indicators of 0.79 and 0.80 fall into the high category. Based on the results of the study, it can be concluded that ADPHYLAB-based learning media can improve student SPS compared to LABSTER-based learning media. Keywords: ADPHYLAB, virtual laboratory, LABSTER, science process skills, atomic spectroscopy. DOI: http://dx.doi.org/10.23960/jpmipa/v25i2.pp932-945